SUFFIXES FORMING ADJECTIVES IN ENGLISH AS FOUND IN OPINION COLUMNS IN THE JAKARTA POST - Bonar Gurning; Karnita Sembiring (Muse: Jurnal of Art, 2024)
This study deals with an analysis of suffixes forming adjective in the opinion columns of The Jakarta Post. Discussing about suffixes forming adjective, we use the theory of Francis Nelson (1958) and Bauer Laurie (1983) to analyze data. Francis and Bauer have twenty-one suffixes forming adjective the suffix (y), (-al}, {- able), (-ful), (-ar), (-ary), (-ic), (-ish), (-ous), (-ent/-ant), (-ed), (ive), (-en), (-ing), (-ly), (-esque), (-ese), (-ate), (- some), (-atory). In accomplishing this study, we firsly, read some books, then collected the data from the opinion columns of The Jakarta Post from December 1"-31, 2001. Later we classifid them according to the suffix they contain, and analyzed them accordingly. The total number of the data is 245 data. .The result of the analysis shows that English suffixes forming adjective in the opinion columns of The Jakarta Post from 1"-31 december, 2001 mostly used the suffix (-al) 55 data, followed by suffix {-ive) 24 data, suffix (-er) 22 data, suffix (-ic) 21 data, suffix (-able) 20 data, suffix {-ful) 15 data, suffix (-est) 12 data, suffix (-less) 12 data, suffix (-ous) 11 data, suffix (-y) 11 data, suffix (-ly) 9 data, suffix (-ary) 9 data, suffix (-ant/-ent) 8 data, suffix (-ed) 7 data, suffix (ing) 6 data, suffix {-ar) 1 data, suffix {-ish) 1 data, suffix {-en) 1 data.